Atmospheric ice nucleation by glassy organic compounds: a review - Salameh, Anastasia; Daskalakis, Vangelis (My University, 2017)
Aerosol particles play a vital role in atmospheric processes and the climate as they facilitate the formation of clouds and precipitation. Secondary organic aerosols (SOA) represent a significant subclass of atmospheric compounds, and recent research revealed that they could exist in a semi-solid or glassy state at low temperatures and relative humidity conditions. Glassy organic compounds influence ice nucleation, ice growth, chemical reactions and water uptake of aerosols have an effect on the pathway of activation of cloud droplets and ice crystals. There are no proposed mechanisms at the atomic level to describe ice nucleation on glassy organic aerosol. The present paper reviews existing knowledge and identify mechanisms regarding glassy organics in atmospheric aerosols and their implications for atmospheric processes that affect climate modeling.
Keywords: Ice Nucleation; Glassy Organics; Secondary organic aerosols; Climate